Penggunaan Metode Bercerita Dalam Kisah Nabi Muhammad di Pengembangan Nilai Keagamaan Pada Anak Usia Dini Usia 4-6 Tahun di TK Rausan Fikri Kabupaten Bekasi - Ayuningtyas, Rahmah; Rahmah Ayuningtyas; Qurota A'yun; Imamah (Pendidikan Guru PAUD, FKIP, Univ Muhammadiyah Tasikmalaya, 2025)
Instilling religious values from an early age is the foundation for forming children’s character. In Islamic education, the method of telling the story of the Prophet Muhammad (PBUH) can be an effective means of instilling these values. This study aims to analyze the use of the method of telling the story of the Prophet Muhammad PBUH in learning Islamic religious education in early childhood at Rausan Fikri Kindergarten, Bekasi Regency, as well as exploring the religious character instilled, the effectiveness of the method, and the factors that influence it. This study uses a qualitative approach with a case study design. Data was collected through participatory observation, in-depth interviews, and documentation. The results of the study show that the application of the storytelling method with a serial approach and the use of visual media can attract children’s attention, increase understanding of the concept of religious values, and foster religious characters such as honesty, patience, affection, tawakal, and love for the Prophet PBUH. Everyday. However, internalizing values must be continuously strengthened because early childhood interests are easily distracted. The child’s internal factors, the teacher’s skills, and support from parents significantly affect the effectiveness of this method. The conclusion of this study underscores the importance of collaboration between teachers and parents in strengthening the cultivation of religious character through fun and contextual storytelling methods.